Pathogen-Specific Binding Soluble Down Syndrome Cell Adhesion Molecule (Dscam) Regulates Phagocytosis via Membrane-Bound Dscam in Crab - Li, Xue-Jie; Yang, Lei; Li, Dan; Zhu, You-Ting; Wang, Qun; Li, Wei-Wei (Frontiers in Immunology, 2018)
The Down syndrome cell adhesion molecule (Dscam) gene is an extraordinary example of diversity that can produce thousands of isoforms, and has so far been found only in insects and crustaceans. Cumulative evidence indicates that Dscam may contribute to the mechanistic foundations of specific immune responses in insects. However, the mechanism and functions of Dscam in relation to pathogens and immunity remain largely unknown. In this study, we identified the genome organization and alternative Dscam exons from Chinese mitten crab, Eriocheir sinensis. These variants, designated EsDscam, potentially produce 30,600 isoforms due to three alternatively spliced immunoglobulin domains (Igs) and a transmembrane domain (TM). EsDscam was significantly upregulated after bacterial challenge at both mRNA and protein levels. Moreover, bacterially-induced specific EsDscam isoforms were found to bind specifically with the original bacteria to facilitate efficient clearance. Furthermore, bacteria-specific binding of soluble EsDscam via the complete Ig1-Ig4 domain significantly enhanced elimination of the original bacteria via phagocytosis by hemocytes; this function was abolished by partial Ig1-Ig4 domain truncation. Further studies showed that knockdown of membrane-bound EsDscam inhibited the ability of EsDscam with the same extracellular region to promote bacterial phagocytosis. Immunocytochemistry indicated co-localization of the soluble and membrane-bound forms of EsDscam at the hemocyte surface. Far-Western and co-immunoprecipitation assays demonstrated homotypic interactions between EsDscam isoforms. This study provides insights into a mechanism by which soluble Dscam regulates hemocyte phagocytosis via bacteria-specific binding and specific interactions with membrane-bound Dscam as a phagocytic receptor.